OPTIMIZATION OF VILLAGE TOURIST ATTRACTIONS THROUGH VOLUNTOURISM AND GREEN HOMESTAY GOVERNANCE BASED ON LOCAL WISDOM IN KANDANGAN VILLAGE, SENDURO DISTRICT, LUMAJANG REGENCY - Bambang Suharto; Novianto Edi Suharno; Sri Endah Kinasih; Syarifuddin Hidayatullah; Mikhail Vins Louis Limanto; Dian Mifthakhul Jannah; Silvi Kurrotul Aini; Zahara Salsabila; Syamsul Pahmi; Reni Juliani (Jurnal Layanan Masyarakat (Journal of Public Services), 2026)
This community service study aims to strengthen tourism governance in Kandangan Village, Senduro District, Lumajang Regency, through the integration of a Voluntourism approach and the development of Green Homestays grounded in Tengger local wisdom. The method employed consists of interactive training integrated with field-based practices involving BUMDes, Pokdarwis, homestay owners, and the local community. The program focuses on strengthening village tourism institutions, fostering innovation in voluntourism-based tourism products, and facilitating the transformation of conventional Homestays into Green Homestays. Program evaluation was conducted using pretest and posttest instruments to measure improvements in participants’ knowledge and understanding of Green Homestay principles. The results indicate that 77% of participants experienced an increase in understanding, demonstrating the effectiveness of the training in enhancing community capacity. This study contributes to the development of a Green Homestay governance model that integrates environmentally responsible practices with local cultural values, while also reinforcing Voluntourism as a strategy for community-based tourism development. The findings affirm that institutional collaboration and active community participation are key determinants in achieving economically, socio-culturally, and environmentally sustainable and competitive village tourism.